STRATEGI PENGEMBANGAN BISNIS BIOINSEKTISIDA CV THARA NERO TAMA-JEMBER - Ranti Heri Risma Wati; Tanti Kustiari; Ujang Suryadi (UNIVERSITAS LANCANG KUNING, 2018)
Bioinsecticide has known for much farmers to substitute chemical pesticide. In periodically, hope that can reduce negative impact from chemical pesticide. One of company that starts their business with fertiliser and biology pesticide is CV Thara Nero Tama. This company was make business from made by order system, but now company wants to build their business more. The research aimed to priority of strategy from their internal and external factor. This research used Quantitative Strategic Planning Matrix (QSPM) method with determine alternative strategies, than decide priority strategy. For the method stages are input stage with IFE and EFE matrix, continued with matching stage, IE matrix. The last stage is decision stage with QSPM method. Based on the result, the alternative strategies that can applied is seven strategies with highest TAS (Total Attractive Score) was the improving market segmentation.